Xanthates As Useful Probes for Testing the Active Sites of Cytochromes P450 4A11 and 2E1 - Stoyanova, Tsveta; Lessigiarska, Iglika; Mikov, Momir; Pajeva, Ilza; Yanev, Stanislav (Frontiers in Pharmacology, 2017)
Xanthates (alkyl or aryl derivatives of dithiocarbonic acid) have been shown to be selective mechanism-based inactivators of cytochromes P450 2B1/2B6 and 2E1 due to covalent binding of a reactive intermediate to apoprotein after double hydrogen abstraction at α-carbon atom, suggesting interaction of the xanthate dithiocarbonic head with the enzyme heme. The structures of xanthates with a long alkyl chain are similar to the fatty acids. Saturated fatty acids (FA) such as lauric acid (LA), are metabolized by different cytochrome P450 isoforms to ω- and (ω-1)-hydroxy products, in humans done by CYP4A11 and CYP2E1, respectively. In the present study we aimed at elucidating the possible interactions of xanthates with two cytochrome P450 isoforms CYP4A11 and CYP2E1 involved in the metabolism of the FA. Our experiments showed that LA-ω-hydroxylation by CYP4A11 is inhibited in a competitive manner by xanthates with long alkyl chain (C12-xanthate being the most potent inhibitor). On the other hand LA-(ω-1)-hydroxylation reaction by purified CYP2E1 is inactivated by a mechanism-based type. The suggested differences in the interactions of C12-xanthate with the two cytochrome P450 isoforms were investigated by molecular modeling using docking approach. The results suggested that in CYP2E1 active site C12-xanthate coordinates to the heme with its most vulnerable dithiocarbonic head leading to a mechanism-based inactivation. In CYP4A11 xanthate alkyl chain is exposed to the heme, thus, a potenial ω-hydroxylated xanthate product could be formed, which could inhibit in a competitive manner the hydroxylation of LA. The observed differences of xanthates interactions with the active sites of the two similar cytochrome P450 isoforms (CYP4A11 and CYP2E1) involved in the metabolism of FA, which lead to different changes in the enzyme activity, suggest that xanthates can be used as probing tools for analyzing enzyme active sites when exploring useful and selective compounds influencing FA homeostasis.